RENCANA STRATEGI BISNIS PT. HINOKA ALSINDO TEKNI - Irfan Arif Husen Husen (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2016)
Study aims to provide an overview of the company's chosen strategy to the management of PT. Hinoka Alsindo Tekni (PT. HAT) for the years 2014-2017.This research was conducted with the concept of strategic management to analyze the external and internal factors PT. HAT in the agricultural machinery industry. External factors macro with PESTE analysis and industry analysis with the analysis of the five forces of competition. Once it is known the opportunities and threats that put in a matrix of External Factor Evaluation (EFE). For the analysis of internal factors Competitive Profile Matrix (CPM) and functional analysis. After the known strengths and weaknesses are incorporated into the matrix of the Internal Factor Evaluation (IFE). EFE matrix values of 2.27 and a value 2.48 IFE matrix which is to be in quadrant V in the matrix Internal External (IE) that hold and maintain strategy. After appearing several alternative strategies through TOWS matrix then grouped into two strategic priorities, namely market penetration and product development are assessed based on the analysis QSPM. Results from this study is the implementation of appropriate strategies and targeted activities during the years 2014-2017.